2020
DOI: 10.1155/2020/3076463
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Rate of Type 2 Diabetes Mellitus after Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis of 170,139 Women

Abstract: Objective. The reported incidence of type 2 diabetes mellitus (T2DM) after gestational diabetes (GDM) varies widely. The purpose of this meta-analysis was to define the incidence rate of T2DM among women with a history of GDM and to examine what might modulate the rate. Research Design and Methods. We searched PubMed and Embase for terms related to T2DM after GDM up to January 2019. Large cohort studies with sample size ≥300 and follow-up duration of at least one year were included. Data from selected studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 59 publications
6
108
1
8
Order By: Relevance
“…Women of reproductive age with prediabetes may develop type 2 diabetes by the time of their next pregnancy and will need preconception evaluation. Because GDM is associated with an increased lifetime maternal risk for diabetes estimated at 50-60% (107,108), women should also be tested every 1-3 years thereafter if the 4-12 weeks postpartum 75-g OGTT is normal. Ongoing evaluation may be performed with any recommended glycemic test (e.g., annual A1C, annual fasting plasma glucose, or triennial 75-g OGTT using nonpregnant thresholds).…”
Section: Postpartum Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Women of reproductive age with prediabetes may develop type 2 diabetes by the time of their next pregnancy and will need preconception evaluation. Because GDM is associated with an increased lifetime maternal risk for diabetes estimated at 50-60% (107,108), women should also be tested every 1-3 years thereafter if the 4-12 weeks postpartum 75-g OGTT is normal. Ongoing evaluation may be performed with any recommended glycemic test (e.g., annual A1C, annual fasting plasma glucose, or triennial 75-g OGTT using nonpregnant thresholds).…”
Section: Postpartum Follow-upmentioning
confidence: 99%
“…Women with a history of GDM have a greatly increased risk of conversion to type 2 diabetes over time (108). Women with GDM have a 10-fold increased risk of developing type 2 diabetes compared with women without GDM (107).…”
Section: Gestational Diabetes Mellitus and Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with GDM have a higher risk of cesarean section, pregnancy induced hypertension [5][6][7], as well as developing type 2 diabetes mellitus (T2DM) after delivery [8][9][10][11]. Offsprings with in utero exposure to GDM have increased rates of large for gestational age [12,13], macrosomia [14], and early onset cardiovascular disease from childhood to early adulthood [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) identifies women who have a defect in β‐cell function, such that they are unable to secrete sufficient insulin to fully compensate for the insulin resistance of pregnancy 1 . Our previous study showed that the risk of developing type 2 diabetes in women with previous GDM increased linearly by 9.6‰ for every additional 1 year of follow up, and almost one‐fifth of women with GDM would develop type 2 diabetes when the follow‐up duration extended to 10 years 2 . Even in the early postpartum period, women with a diagnosis of GDM are up to 50% likely to develop glucose intolerance 3 .…”
Section: Introductionmentioning
confidence: 99%